In situ characterization of one-dimensional plasmonic Ag nanocluster arrays - SHVETS, IGOR; FLEISCHER, KARSTEN; MCGILP, JOHN (My University, 2011)
One-dimensional Ag nanoparticle arrays have been grown on step-bunched vicinal Al2O3 in ultrahigh vacuum using deposition at a glancing angle. The structures grown showed a strong optical anisotropy in the visible region of the spectrum. The optical anisotropy was measured in situ using reflection anisotropy spectroscopy. Relevant optical properties were determined as a function of deposition angle and Ag thickness. A simple phenomenological model was developed to reproduce the features seen in the spectra. With this model it was possible to use the inhomogeneous broadening as a guide to the nanoparticle dispersion
PUBLISHED
Keywords: nanoparticle dispersion; nanoparticle dispersion; Nanoscience & Materials